Early-Phase Adverse Effects and Management of Liposomal Amikacin Inhalation for Refractory Mycobacterium avium Complex Lung Disease in Real-World Settings - Morita A; Namkoong H; Yagi K; Asakura T; Hosoya M; Tanaka H; Lee H; Ogawa T; Kusumoto T; Azekawa S; Nakagawara K; Kamata H; et al. (Infection and Drug Resistance, 2022)
Atsuho Morita,1 Ho Namkoong,2 Kazuma Yagi,1 Takanori Asakura,1 Makoto Hosoya,3 Hiromu Tanaka,1 Ho Lee,1 Takunori Ogawa,1 Tatsuya Kusumoto,1 Shuhei Azekawa,1 Kensuke Nakagawara,1 Hirofumi Kamata,1 Makoto Ishii,1 Koichi Fukunaga,1 Hiroyuki Ozawa,3 Naoki Hasegawa2 1Division of Pulmonary Medicine, Department of Medicine, Keio University School of Medicine, Tokyo, Japan; 2Department of Infectious Diseases, Keio University School of Medicine, Tokyo, Japan; 3Department of Otorhinolaryngology, Head and Neck Surgery, Keio University School of Medicine, Tokyo, JapanCorrespondence: Ho Namkoong, Department of Infectious Diseases, Keio University School of Medicine, Tokyo, Japan, Tel +81 03 3353 1211, Fax +81 03 5843 6167, Email hounamugun@gmail.comPurpose: Amikacin liposome inhalation suspension (ALIS), which efficiently allows amikacin to reach the pulmonary periphery for effect while minimising systemic adverse effects, was recently approved for treating Mycobacterium avium complex (MAC) infections. The international Phase 3 open-label clinical trials showed promising results, contributing to sputum culture conversion, but few studies have examined the efficacy and adverse effects of ALIS using real-world data. We identified the clinical outcome and adverse effects of ALIS in the early phase of treatment, for more effective and safe use in clinical practice.Patients and Methods: The study population consisted of patients with MAC lung disease (MAC-LD), introduced to ALIS therapy after July 2021 at Keio University Hospital due to poor response to multidrug therapy. The sputum smear/culture results, symptoms, adverse effects, and the serum amikacin concentrations of the early phase of ALIS inhalation therapy were examined.Results: A total of 11 patients (9 women; median age 64.6 years) were included in this study. The median disease duration of MAC-LD was 13.7 years, and all patients exhibited a positive culture at the beginning of ALIS inhalation. Three of the six patients (50.0%) who were initially sputum-smear-positive were confirmed to have become sputum-smear-negative within one month, including one culture conversion. ALIS inhalation therapy caused some adverse effects in nine patients (81.8%); however, no serious systemic adverse effects were observed. The most common adverse effect was hoarseness (72.7%), which mostly occurred around 1 week after initiation. The medians of peak serum amikacin concentrations were 1.4 and 2.3 μg/mL for the first and third inhalations, respectively. Trough serum concentrations just before the third inhalation were < 1.2 μg/mL in all patients.Conclusion: ALIS therapy might be a treatment option for patients with refractory MAC infection with long disease duration and a poor response to guideline-based therapy.Keywords: Mycobacterium avium complex, MAC, nontuberculous mycobacteria, NTM, amikacin liposome inhalation suspension, ALIS